Effect of manganese oxide dopant and sintering on the properties of scandia stabilized zirconia / Ng Chui Kim - Ng , Chui Kim (2018)
Oxide ion conductors have important applications in oxygen sensors, pumps and SOFCs. The best-known oxide ion conductor is stabilized zirconia with exclusive ionic conductivity at elevated temperature. An understanding of the impact from the use of dopant on the zirconia ceramic is critical for tailoring the fabrication and high temperature operational stability of these devices. The conventional sintering method is time and energy consuming, in contrast to traditional approaches to heat transfer based on radiation and convection, rapid microwave heating allows volumetric heating, thus a potential alternative sintering route to provide accelerated densification with limited grain growth. This research work investigated the effect of manganese oxide (MnO2) dopant and sintering on the properties of ceria-doped scandia stabilized zirconia (10Sc1CeSZ). Commercially available 10Sc1CeSZ ceramic powder was compared with the powder synthesized via solid state sonication-ball milling method. The results showed that all 10Sc1CeSZ sintered compacts prepared from commercial powder had pure cubic phase, with better resulting mechanical and electrical performance compared to synthesized powder. The effect of MnO2 additions on the properties of 10Sc1CeSZ was investigated and the results showed that the addition up to 1 wt% had negligible effect on the mechanical properties of the ceramic. The samples containing up to 1 wt% MnO2 attained above 97.5 % relative density, Vickers hardness of 13-14 GPa and fracture toughness of 3 MPam1/2. In addition, it was revealed that the 0.5 wt% MnO2 addition was beneficial in suppressing the cubic zirconia grain growth i.e. the highest average grain size was measured at 4.9 μm when sintered at 1550 C as compared to 9.9 μm measured for the undoped zirconia when sintered at the same temperature. On the other hand, the addition of 5 wt% MnO2 was found to be detrimental to the densification and properties of the zirconia, particularly when sintered at higher temperatures. This was attributed to the accelerated grain growth of the doped samples, i.e. the grain size increased by twofold, to 18.6 μm when sintered at 1550 C. In addition, the influence of rapid sintering via microwave technique at low temperature regimes of 1300 C and 1350 C for 15 minutes on the properties of undoped 10Sc1CeSZ was evaluated. It was found that both sintering processes yielded highly dense samples with a minimum theoretical density of 97.5%. All sintered pellets had pure cubic phase and possessed high Vickers hardness (13-14.6 GPa) and fracture toughness (~3 MPam1/2). SEM microstructures revealed that the grain size varied from 2.9-9.9 μm for the conventional-sintered samples. In comparison, the grain size of the microwave-sintered zirconia was maintained below 2 μm. EIS study showed that both the bulk and grain boundary resistivity of the zirconia decreases with increasing test temperature regardless of sintering methods. However, the grain boundary resistivity of the microwave-sintered samples was higher than the conventional-sintered ceramic at 600 C and reduced significantly at 800 C thus resulting in the enhancement of electrical conduction. A sintering mechanism involving preferential grain boundary local heating was proposed for enhanced densification and the resulting sintering properties of the zirconia ceramic. MnO2 was found to be as an effective additive to scavenge siliceous phase at the grain boundary.